Pemodelan Pendukung Keputusan Penentuan Suhu Ideal Susu dalam Pembuatan Yogurt Menggunakan Metode Fuzzy Tsukamoto - Nava Azahra; Arba Rinata; Syafiul Muzid (JURNAL UNITEK, 2025)
The production of yogurt is a fermentation process of milk that is influenced by temperature, especially during pasteurization and fermentation. Temperature inaccuracies can reduce nutritional value and inhibit the growth of starter bacteria such as Lactobacillus bulgaricus. To address this challenge, the research proposes the use of the Fuzzy Tsukamoto method as a decision support system. This method effectively handles linguistic data and uncertainty by considering the variables of pH, fat content, fermentation time, and starter bacteria concentration. As a result, the system can consistently recommend optimal temperatures, which is expected to improve the quality and efficiency of yogurt production, especially in small and medium-sized enterprises.